2004
DOI: 10.1634/stemcells.22-2-202
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis Demonstrates Expansion of SCID‐Repopulating Cells and Increased Engraftment Capacity in Human Cord Blood Following Ex Vivo Culture with Human Brain Endothelial Cells

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 60 publications
3
36
2
Order By: Relevance
“…[7][8][9] Our laboratory has shown that primary human brain-derived endothelial cells produce a soluble hematopoietic activity that supports a 1 to 2 log expansion of the most primitive assayable human hematopoietic cell, which is capable of long-term repopulation in nonobese diabetic/severe combined immunodeficient mice. [10][11][12] Li et al 13 have also confirmed that murine brain-and heart-derived endothelial cells can support the maintenance of colony-forming unit-spleen day-8 colonies in vitro. Taken together, these data implicate vascular endothelial cells as a source of proliferative and regenerative signals for hematopoietic stem and progenitor cells.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…[7][8][9] Our laboratory has shown that primary human brain-derived endothelial cells produce a soluble hematopoietic activity that supports a 1 to 2 log expansion of the most primitive assayable human hematopoietic cell, which is capable of long-term repopulation in nonobese diabetic/severe combined immunodeficient mice. [10][11][12] Li et al 13 have also confirmed that murine brain-and heart-derived endothelial cells can support the maintenance of colony-forming unit-spleen day-8 colonies in vitro. Taken together, these data implicate vascular endothelial cells as a source of proliferative and regenerative signals for hematopoietic stem and progenitor cells.…”
Section: Introductionmentioning
confidence: 93%
“…Although these studies have demonstrated the capacity of endothelial cells to support hematopoiesis in vitro, [7][8][9][10][11][12][13] evidence of the in vivo contribution of endothelial cells to adult hematopoiesis has begun to emerge. Blockade of N-cadherin on vascular endothelial cells in the BM has been associated with delayed megakaryocyte recovery in 5-FUtreated mice, 5 and accelerated repair of this BM vascular niche has been associated with early megakaryocytopoiesis after chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…63 It is currently not known whether non-contact conditions are sufficient for ex vivo expansion or whether stromal binding is required. 64 MSCs have been used in preclinical models as a method to maintain stem cells in an immature state. MSCs give rise to osteoblasts, chondrocytes, adipocytes and myelosupportive stroma.…”
Section: Stromamentioning
confidence: 99%
“…As stromal and endothelial cells have been proposed for some years to sustain HSPCs during culture and are suspected to enhance hematopoietic recovery after cografting in preclinical or clinical models, [11][12][13][14][15][16][17] we evaluated the potential usefulness of MSCs in the ACT context. We have previously shown the capacity of MSCs to cooperate with 4F to reduce apoptosis of CD34 þ cells exposed to doses up to 4 Gy in vitro and to preserve their hematopoietic potential in vitro.…”
mentioning
confidence: 99%